2020
DOI: 10.3390/insects11020089
|View full text |Cite
|
Sign up to set email alerts
|

Wing Geometric Morphometrics of Workers and Drones and Single Nucleotide Polymorphisms Provide Similar Genetic Structure in the Iberian Honey Bee (Apis mellifera iberiensis)

Abstract: Wing geometric morphometrics has been applied to honey bees (Apis mellifera) in identification of evolutionary lineages or subspecies and, to a lesser extent, in assessing genetic structure within subspecies. Due to bias in the production of sterile females (workers) in a colony, most studies have used workers leaving the males (drones) as a neglected group. However, considering their importance as reproductive individuals, the use of drones should be incorporated in these analyses in order to better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…The changes found in more distant geographic groups may reflect genetic aspects among the colonies in the Pantanal (Francoy et al, 2011;Combey et al, 2018;Henriques et al, 2020) or even in relation to resource use in case of some bees (Carneiro et al, 2019;Ribeiro et al, 2019). The slight variation between some points in the Pantanal could be related to the fact that some individuals collected were not from the same colony, that is, individual reflections of other distinct groups within the same collection point.…”
Section: Discussionmentioning
confidence: 99%
“…The changes found in more distant geographic groups may reflect genetic aspects among the colonies in the Pantanal (Francoy et al, 2011;Combey et al, 2018;Henriques et al, 2020) or even in relation to resource use in case of some bees (Carneiro et al, 2019;Ribeiro et al, 2019). The slight variation between some points in the Pantanal could be related to the fact that some individuals collected were not from the same colony, that is, individual reflections of other distinct groups within the same collection point.…”
Section: Discussionmentioning
confidence: 99%
“…This approach showed 100% accuracy for the species identification of the chiggers [ 49 ]. Moreover, this technique was used to analyze species of Apidae bees, Formicidae ants, Ixodidae ticks, Psychodidae sandflies, and Reduviidae bugs [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Advanced Approaches For Medical Parasite and Arthropod Diagnosesmentioning
confidence: 99%
“…The anterior (LM5, LM7, and LM8) and the posterior (LM 18, LM19, and LM20) displacement resulted in a shortening linked to an expansion. The morphological characteristics of honeybees have an important role in discriminating honeybee subspecies (Salehi and Nazemi-Rafie 2020;Henriques et al 2020). It has been reported that different selective pressures shape morphological traits, which is crucial in evolutionary biology.…”
Section: Variations In Wing Shape Among Subspeciesmentioning
confidence: 99%